A synopsis of the subterranean asellids of Maryland, U.S.A., with description of Caecidotea alleghenyensis, new species (Crustacea: Isopoda: Asellota) - Lewis, Julian J.; Bowman, Thomas E.; Feller, Daniel J. (Zootaxa, 2011)
Nine species of asellid isopods are reported from groundwater habitats in Maryland. Three of these species are habitually found in springs: Lirceus brachyurus, Caecidotea kenki, and C. alleghenyensis, n. sp. The latter, described herein, is a member of the hobbsi group known only from the Allegheny Mountains in Garrett Co. Six species are obligate inhabitants of subterranean waters and are found primarily in Appalachian caves, although some have broad ranges that span noncavernous areas. The obligate subterranean species are Caecidotea pricei, C. franzi, C. holsingeri, C. mausi, C. vandeli and C. nordeni.